A Linguist’s Reminiscences to Identification Theory: Epistolary of Panteleimon Kulish. Article 2 - Shevchenko , Larysa (Current issues of Ukrainian linguistics: theory and practice, 2019)
The article is devoted to the analysis of the complex process of evolution of Panteleimon Kulish’s worldview. Panteleimon Kulish was a polyphonic personality who left in the history of the Ukrainian culture the heritage of a writer, publisher and translator. P. Kulish’s epistolary and creative work are investigated in the categories of E. Erickson’s theory, which has become an intellectual matrix for understanding the processes of a subject’s development in certain psychosocial conditions and circumstances. In E. Erickson’s theory of identification the article analyses the epistolary of Panteleimon Kulish – an outstanding Ukrainian culturologist, publisher, writer and translator. The author states that E. Erickson’s theory created the intellectual matrix of a person’s development analysis in the system of psychosocial conditions and circumstances. The scholar studies E. Erickson’s main postulate, namely the correlation of a personality with psychosocial identity. The stages of evolution of P. Kulish’s national self-consciousness (from assertion of slavophilе positions in his youth to evolutionary extension of the author’s worldview) are considered. Accordingly, the dominant of the artist’s Ukrainian-centricity, enrichment of his worldview with European ideas, ideals, cultural facts and, as a consequence, a formed outlook with understanding of the identification perspective of the nation in European history and culture are analyzed. The major problem in the analysis of P. Kulish’s creative person is the problem of ethnic identification. The article explores the criteria of P. Kulish’s ethnic identification: existential choice, ways of self-realization, achievement of internal freedom, solving individual-psychological problems of belonging to a certain social strata, realization of a person’s powerful intentions in the national language. The analytics of the article is based on P. Kulish’s epistolary that is a representative form of the author’s communication with the leading writers and public figures of the Slavic world in the middle of the 19th century. The epistolary enables to build a panorama of ideas and concepts that have been developed by intellectuals in the context of analyzing the problem of national identity.